2015
DOI: 10.1002/ana.24469
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific antibodies reveal distinct subcellular localizations of C9orf72 in amyotrophic lateral sclerosis

Abstract: Objective: A noncoding hexanucleotide repeat expansion in C9orf72 is the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). It has been reported that the repeat expansion causes a downregulation of C9orf72 transcripts, suggesting that haploinsufficiency may contribute to disease pathogenesis. Two protein isoforms are generated from three alternatively spliced transcripts of C9orf72; a long form (C9-L) and a short form (C9-S), and their function(s) are largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(209 citation statements)
references
References 50 publications
13
193
1
1
Order By: Relevance
“…Protocols were evaluated based on total protein extraction and signal from C9ORF72 peptides. The low salt protocol without detergent resulted in low protein extraction yield and no signal for C9ORF72 peptides, although Western blot signal was previously reported for the short isoform (Xiao et al, 2015). Signals were observed for the three quantitative peptides selected for quantification (peptides 1–3) when applying the Triton containing mixtures, the latter showing higher intensity than that containing urea ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Protocols were evaluated based on total protein extraction and signal from C9ORF72 peptides. The low salt protocol without detergent resulted in low protein extraction yield and no signal for C9ORF72 peptides, although Western blot signal was previously reported for the short isoform (Xiao et al, 2015). Signals were observed for the three quantitative peptides selected for quantification (peptides 1–3) when applying the Triton containing mixtures, the latter showing higher intensity than that containing urea ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 84%
“…Protein extraction protocols with tissue homogenization by mechanical shear recently published for C9ORF72 (Xiao et al, 2015), containing either low/high-salt content (i.e., 150 mM NaCl or 750 mM NaCl), 8 M urea or Triton X-100, were individually evaluated on tissues samples from frontal cortex ( Figure 4 ). These protocols were adapted to single use bead-beating Precellys tubes to parallelize protein extraction and avoid contamination between samples.…”
Section: Resultsmentioning
confidence: 99%
“…These include haploinsufficiency, toxic RNA interfering with the function of RNA-binding proteins or other cellular factors, and the presence of toxic dipeptide repeat proteins through Repeat-associated non-ATG (RAN) translation 25 26. Recent work has also pointed towards C9orf72 -induced pathology of nucleocytoplasmic transport processes 26–29.…”
Section: Discussionmentioning
confidence: 99%
“…Both C9orf72 mRNA and the C9orf72 protein are highly expressed in the brain in mice and humans 38. Studies have reported lower levels of C9orf72 mRNA in patients carrying the expansions and reductions in the long C9orf72 isoform 39. However, the short isoform seems to accumulate at higher levels and relocalise to the plasma membrane, suggesting a potential mechanism of toxicity, although the significance of these findings is unclear.…”
Section: C9orf72 and Mechanisms Of Toxicitymentioning
confidence: 99%